Comparison Curriculum Analysis between Indonesian KTSP 2006 and 2013 Curriculums - Barata, Alvin; Patria, Lilis; Shilvani, Shilvani (Proceedings International Conference on Teaching and Education (ICoTE), 2024)
Education has become a part of human life. It is given to individuals differently depending on where the educational activities take place. In order to maintain the consistency of education in certain areas, there is a need for a curriculum that defines the materials and learning standards that must be taught and achieved in educational institutions based on the customs of each area around the world. One method of curriculum implementation is through textbooks. They are tools in which curriculum materials and standards are implemented to support teaching and learning activities. Textbooks always have problems with the content related to the implemented curriculum. There is a need for evaluation to assess the effectiveness and efficiency of textbooks. This study examines the existing implemented curriculum with the textbook contents. Two textbooks, "Bahasa Inggris" based on Indonesian Curriculum 2013 and "Developing English Competences" based on Indonesian KTSP 2006 curriculum, are used for assessment and evaluation. Qualitative method called document analysis is used by implementing McGrath's theory to evaluate textbooks. The results are the difference and validity between the textbooks contents and both the 2013 and 2006 KTSP curriculum. Both are considered suitable, but with some difficulties in certain degrees in teaching and learning activities.